Impact of participatory silvipastoral intervention and soil conservation measures for forage resource enhancement in western Himalaya - DEV, INDER; RADOTRA, SUDESH; KHOLA, O P S; MISRI, BIMAL; SAREEN, SINDHU; SINGH, J P; SRIVASTAVA, A K; SINGH, BHUPINDER; SHARMA, S K; CHAMOLI, K P; KUMAR, DINESH (The Indian Journal of Agricultural Sciences, 2014)
Livestock rearing is an important component of rural economy in mid-hills of Himalaya. Inspite of abundant available feed resources, total available biomass is insufficient to sustain the livestock population. Fodder trees particularly in hill ecosystem play an important role in supplementing the fodder requirement especially during the lean period. Information gathered and analysis concludes that Grewia optiva is the most important fodder tree in terms of dominance, palatability and increase in milk yield followed by Artocarpus chaplasha, Morus alba, Bauhinia variegata, Albizia lebbeck and Terminalia alata in Kangra and Mandi districts of Himachal Pradesh. The crude protein content was found highest in Grewia optiva (19.38%) followed by Albizia lebbeck (18.85%), Dendrocalamus hamiltonii (18.01%) and minimum in case of Quercus incana (9.27%). During scarcity of fodder Ficus religiosa is the only fodder tree fed throughout the year. The established silvipasture produced leaf biomass of 2.77 to 6.77 DM kg/tree (Ghanetta), 2.12 to 5.96 DM kg/tree (Jogindernagar) and 2.25 to 6.93 DM kg/tree (Dagoh). Fodder trees planted under silvipastoral system produced average biomass of 1.83 DM tonnes/ha (Ghanetta), 1.49 DM tonnes/ha (Jogindernagar) and 1.66 DM tonnes/ha (Dagoh). Rainfall events of more than 50 mm, though quite less in number (25/165, 24/192 and 17/149), contributed 47.7, 82.3 and 81.7% to the total runoff at Ghanetta, Jogindernagar and Dagoh, respectively. Among the resource conservation measures trenching in combination with vegetative barrier allowed only 8.2% of rain as runoff compared to 41.5% under control (no measure). The silvipasture systems coupled with contour staggered trenches and / or vegetative barrier can effectively arrest the environmental degradation.